Dampak Sikap Narsistik Siswa Terhadap Hubungan Sosial Di Mts Zia Salsabila - Ade Chita Putri Harahap; Addilla Addilla; Nur Fadillah Butar-Butar; Lania Rojannah Siregar; Ivo Liza Miranda; Dinda Asmidar Tanjung; Silvi Duwi Nitami (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
Narcissistic attitudes usually develop in adolescence, where students are looking for self-identity and pay attention to their self-image. Second, social media and popular culture that highlight self-interest and public recognition can also reinforce narcissistic attitudes. Third, the impact of students' narcissistic attitudes can affect their social relations with other people, both in the family, school and community environment. In the school environment, students with narcissistic attitudes tend to pay less attention to the needs and feelings of others, and to focus more on themselves. This can make it difficult for these students to work together in groups or teams, because they tend to want to be the center of attention and take over decisions. In the long term, this can hinder students' ability to develop social skills and build healthy interpersonal relationships. In addition, students with narcissistic attitudes may also experience difficulties in maintaining their social relationships with peers. They tend to be less sensitive to other people's feelings and more easily see others as tools to achieve their own goals. This can cause conflict and tension in social relationships, as well as make it difficult for students to build closeness and trust with others.